Post Dengue Depression and It’s Associated Factors Among Bangladeshi Population; Observation From a Tertiary Care Medical College Hospital - Abhizit Pandit; Ishrat Jabeen; Avijit Sarker Jyoti; Arnab Kumar Ghosh; Sofura Nammi Kristy; Arpita Sarkar Proma; Moshfiqua Mehnaz; Tasnuva Tahrin Tamanna (International Journal of Family Medicine and Public Health, 2025)
Background: Dengue, also known as tropical flue has become endemic in many Asian countries including Bangladesh. Dengue disease still lacks of research especially mental health concerns during post infection period. Therefore, the present study investigates the prevalence of post dengue depression and it’s associated factors among the Bangladeshi adult population. Methods and materials: A cross sectional descriptive observational study was conducted among the dengue infected patients, within 1-3 months following discharge from hospital. Information was collected through a pre-structured questionnaire via face-to-face interview where depression during post dengue infection state was assessed by PHQ-9 and data were analyzed with SPSS V-25. Prevalence of post dengue depression and it’s associative factors were explored by appropriate statistical test. Results: A total number of 246 participants were included in our study. Majority (37.9%) were aged 18-29 years, city dwellers (82.1%), married (77.6%), and Muslim (89.4%). All respondents (100%) had other earning members in their families, and the majority (52%) reported a family income between 10,001 and 20,000 BDT. About 35% participants were reported having depression in their post infection state within 1-3 months of follow-up following their discharge from hospital. Among the post infection depressed population, 27% were male and 73 % were female. Sex, monthly family income, Hospitalization days, leave of work due to illness, estimated total cost for treatment were statistically significant(p